Interaction of H2O with CO: potential energy surface, bound states and scattering calculations. Issue 8 (27th October 2017) - Kalugina, Y. N.; Faure, A.; van der Avoird, A.; Walker, K.; Lique, F.
Abstract : We present the first scattering calculations for the H2 O–CO system based on a high accuracy potential energy surface. Abstract : Collisions between H2 O and CO play a crucial role in the gaseous component of comets and protoplanetary disks. We present here a five-dimensional potential energy surface (PES) for the H2 O–CO collisional complex. Ab initio calculations were carried out using the explicitly-correlated closed-shell single- and double-excitation coupled cluster approach with the non-iterative perturbative treatment of triple excitations [CCSD(T)-F12a] method with the augmented correlation-consistent aug-cc-pVTZ basis sets. The most stable configuration of the complex, where the carbon atom of CO is pointing towards the OH bond of water, has a binding energy D e = 646.1 cm −1 . The end-over-end rotational constant of the H2 O–CO complex was extracted from bound state calculations and it was found to be B 0 = 0.0916 cm −1, in excellent agreement with experimental measurements. Finally, cross sections for the rotational excitation of CO by H2 O are computed for s-wave ( J = 0) scattering at the full close-coupling level of theory. These results will serve as a benchmark for future studies.